2021
DOI: 10.3389/fphar.2021.702057
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Outcomes After Dental Extraction in Patients Under Direct-Acting Oral Anticoagulants vs. Vitamin K Antagonists: A Systematic Review and Meta-Analysis

Abstract: Background: The current systematic review aimed to compare bleeding outcomes in dental extraction patients receiving uninterrupted Direct-acting oral anticoagulant (DOAC) or Vitamin K antagonists (VKAs) for various systemic diseases.Methods: PubMed, Embase, ScienceDirect, CENTRAL, and Google Scholar databases were searched for randomized controlled trials, controlled clinical trials, prospective and retrospective cohort studies, and case control studies, conducted on adult patients undergoing dental extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The authors concluded that the accumulating data on management strategies strongly favour continuing anticoagulation before, during, and immediately after invasive dental procedures [ 6 ]. Collectively, the evidence in this review and other studies suggests similar or reduced bleeding risk during dental procedures with NOACs vs VKAs [ 6 , 7 , 14 16 ]. Notably, these studies generally did not describe management strategies aside from continuous anticoagulation and were not able to distinguish whether interruption patterns varied by anticoagulant [ 6 , 7 , 14 16 ].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The authors concluded that the accumulating data on management strategies strongly favour continuing anticoagulation before, during, and immediately after invasive dental procedures [ 6 ]. Collectively, the evidence in this review and other studies suggests similar or reduced bleeding risk during dental procedures with NOACs vs VKAs [ 6 , 7 , 14 16 ]. Notably, these studies generally did not describe management strategies aside from continuous anticoagulation and were not able to distinguish whether interruption patterns varied by anticoagulant [ 6 , 7 , 14 16 ].…”
Section: Discussionmentioning
confidence: 58%
“…Notably, these studies generally did not describe management strategies aside from continuous anticoagulation and were not able to distinguish whether interruption patterns varied by anticoagulant [ 6 , 7 , 14 16 ]. While most studies recommended continuing anticoagulation through dental procedures, clinical practice regarding edoxaban management varied by procedure type, and some form of interruption was common, underscoring the need for studies reporting interruption patterns and outcomes of dental procedures for individual NOACs [ 6 , 7 , 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Wenbing Hua et al . ( 16 ) has reported that the outcomes for bleeding was less excessive for patients taking DOACs in comparison with the group of VKAs patients and the bleeding risk was also lower. One of the limitations of the present review is that the hemostatic measures are different in the studies, which can influence the bleeding rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, for low-risk dental or oral procedures, both VKAs such as warfarin and DOACs may be safely continued unless the patients are on multiple medications or with renal insufficiency [ 40 ]. In the context of bleeding risk following dental procedures, there are mixed reports that DOACs are safer to use than VKAs [ 41 , 42 ], with data supporting better outcomes of post-procedural bleeding with DOACs and concomitant use of local hemostatic agents [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%